Beach Cleanup and Environmental Education at Teluk Bidara Beach, Seberang Pintasan, Dungun, Terengganu, Malaysia - Nabila, Rifda; Guritno, Agung (Nur Science Institute, 2025)
Teluk Bidara Beach is located in Seberang Pintasan Village, Dungun, Kuala Terengganu, Malaysia. Teluk Bidara Beach is one of the tourist destinations on the east coast of Malaysia which has stunning natural beauty. However, behind its beauty there is still a lot of plastic waste littering the beach area. This trash not only destroys the beauty of nature but also endangers the surrounding marine ecosystem. Therefore, a beach cleanup and environmental awareness education was carried out through direct education methods and waste sorting activities in collaboration with the Geng Plastik Ija (GPI) community. This activity succeeded in collecting around 171.65 kg of plastic waste and 29.29 kg of glass bottles. The impact of this activity is the increasing awareness of the community in protecting the beach environment which will make the beach clean, comfortable and increase the attractiveness of tourists to the beach so that economic growth in the area will increase.